When the Ideal Meets the Feasible: Constructing a Protocol for Developmental Assessment at Early School-Age - Farhi, Adel; Glasser, Saralee; Frank, Shay; Hirsh-Yechezkel, Galit; Brinton, Louise; Scoccia, Bert; Ron-El, Rafael; Lerner-Geva, Liat; Gabis, Lidia V. (Frontiers in Pediatrics, 2018)
Objective: To describe development of a methodology for an outcome study of children born following in-vitro fertilization or spontaneously-conceived, as a model for defining normal and below-normal development of school-age children for research purposes. Study Design: The main issues addressed were defining the major health and developmental domains to be investigated, selection of age-appropriate validated instruments, considering time constraints to maximize compliance, and budgetary limitations. The final protocol included a half-hour structured telephone interview with mothers of all 759 children and a 2-hour developmental assessment of 294 of them. Each of the instruments and recruiting methods are described in terms of the abovementioned considerations. Results: Almost all of the mothers who agreed to be interviewed completed it within the half-hour allotted; however only about half of those who agreed to bring the child for the developmental assessment actually did so. The entire examination battery, assessing cognitive ability, executive functions, attention, and learning skills, was completed by almost all 294 children. There was a significant degree of agreement between the maternal report of the child's reading, writing and arithmetic skills and the in-person examination, as well as regarding the child's weight and height measurements. Conclusion: The findings lend support for a low-budget study, relying on telephone interviews. However, limitations such as the validity of maternal report and recall bias must be taken into consideration.